Disposition and Pharmacology of a GalNAc3-conjugated ASO Targeting Human Lipoprotein (a) in Mice - Rosie Z Yu; Mark J Graham; Noah Post; Stan Riney; Thomas Zanardi; Shannon Hall; Jennifer Burkey; Colby S Shemesh; Thazha P Prakash; Punit P Seth; Eric E Swayze; Richard S Geary; et al. (Elsevier, 2016)
Triantennary N-acetyl galactosamine (GalNAc3)-conjugated antisense oligonucleotides (ASOs) have greatly improved potency via receptor-mediated uptake. In the present study, the in vivo pharmacology of a 2'-O-(2-methoxyethyl)-modified ASO conjugated with GalNAc3 (ISIS 681257) together with its unmodified congener (ISIS 494372) targeting human apolipoprotein (a) (apo(a)), were studied in human LPA transgenic mice. Further, the disposition kinetics of ISIS 681257 was studied in CD-1 mice. ISIS 681257 demonstrated over 20-fold improvement in potency over ISIS 494372 as measured by liver apo(a) mRNA and plasma apo(a) protein levels. Following subcutaneous (SC) dosing, ISIS 681257 cleared rapidly from plasma and distributed to tissues. Intact ISIS 681257 was the major full-length oligonucleotide species in plasma. In tissues, however, GalNAc sugar moiety was rapidly metabolized and unconjugated ISIS 681257 accounted > 97% of the total exposure, which was then cleared slowly from tissues with a half-life of 7-8 days, similar to the half-life in plasma. ISIS 681257 is highly bound to plasma proteins (> 94% bound), which limited its urinary excretion. This study confirmed dose-dependent exposure to the parent drug ISIS 681257 in plasma and rapid conversion to unconjugated ASO in tissues. Safety data and the extended half-life support its further development and weekly dosing in phase 1 clinical studies.